Ecology and biogeography in 3D: The case of the Australian Proteaceae - Pausas, J.; Lamont, Byron (Blackwell Publishing, 2018)
The key biophysical pressures shaping the ecology and evolution of species can be broadly aggregated into three dimensions: environmental conditions, disturbance regimes and biotic interactions. The relative importance of each dimension varies over time and space, and in most cases multiple dimensions need to be addressed to adequately understand the habitat and functional traits of species at broad spatial and phylogenetic scales. However, it is currently common to consider only one or two selective pressures even when studying large clades. We illustrate the importance of the all-inclusive multidimensional approach with reference to the large and iconic plant family, Proteaceae: we review life-history traits related to these three dimensions for the 46 genera occurring in Australia and show that this family can be considered the product of a long history of harsh environments, recurrent fires and strong faunal interactions. Because most Proteaceae species occur in fire-prone ecosystems and possess fire-adaptive traits that are both ancient and essential for their survival, disturbance by fire is likely to explain much of this family's ecology, evolution and distribution. Approaches that only examine prevailing environmental variables may fail to identify the mechanisms that drive a taxon's biogeography; they need to consider the likely mechanisms of adaptation and accept or reject plausible alternative hypotheses as the evidence allows. As multidisciplinary teams that consider all aspects of a taxon's ecology are assembled, and databases and numerical tools become increasingly available, studies on the ecology, biogeography and diversity of organisms at broader spatial and phylogenetic scales will arrive at more realistic conclusions.